Pengaruh Partisipasi Penyusunan Anggaran terhadap Kinerja Manajerial (Studi Empiris pada Kantor Pusat Perusahaan Daerah Bank Perkreditan Rakyat (PD. BPR) Garut) - Wati Susilawati; Dida Farida Latipatul Hamdah; Usep Saepudin (Fakultas Ekonomi Universitas Garut, 2019)
The purpose of this study was to determine the effect of budgeting participation on managerial performance at the head office of the local credit bank (PD. BPR) Garut. This study uses primary data through descriptive analysis methods with quantitative method approaches. The data was obtained by sampling techniques using Slovin formula. The data collection of this study uses a questionnaire survey. The questionnaire was submitted to 30 structural employees at PD. BPR Garut headquarters. PD. BPR Garut, as many as 30 questionnaires returned and 30 questionnaires filled in completely, clearly and can be processed. The results of this study indicate that there is a significant influence on budgeting participation at the head office of the local credit bank regional company (PD. BPR) Garut. There is a significant influence of managerial performance at the head office of the local credit bank (PD. BPR) Garut very well and budgetary participation influences managerial performance at the head office of the local credit bank (PD. BPR) Garut.